A model of destructive entrepreneurship - Sameeksha Desai; Zoltan Acs; Utz Weitzel (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
The current research on entrepreneurship as an economic phenomenon often assumes its desirability as a driver of economic development and growth. However, entrepreneurial talent can be allocated among productive, unproductive, and destructive activities. This process is theorized as driven by institutions. Although the tradeoff between productive and unproductive entrepreneurship has been examined, destructive entrepreneurship has been largely ignored. We build from existing theory and define destructive entrepreneurship as wealth-destroying. We propose three assumptions to develop a model of destructive entrepreneurship that presents the mechanisms through which entrepreneurial talent behaves in this manner. We present four key propositions on the nature and behavior of destructive entrepreneurship. We conclude by identifying policy and research streams that emerge from our model.
Keywords: O1; L26; P00; 330; destructive entrepreneurship; entrepreneurship; allocation; rent-seeking; incentives; informal institutions